DECISION-MAKING IVA TEST IN GENDER POWER RELATIONS MARRIED WOMEN - Yanti, Noor Ridha; Tanwiriah; Negara, Candra Kusuma (Sean Institute, 2022)
Gender power in reducing the risk of cervical cancer needs serious attention because it has a role in decision-making in the household. Many women leave all decision-making in the family to their husbands, even regarding their reproductive health problems, because of the power relations that a husband has as the head of the household. Factors of domination of power in the household, socioeconomic and patriarchal culture are some factors that relate to decision-making for women. This study analyzed the relationship between gender power relations and decision-making to conduct an IVA TEST examination. This type of research is an analytical survey with a cross-sectional research design. The study sample was taken by 100 respondents using probability sampling techniques with a simple random sampling type. The results of the bivariate analysis using the chi-square test obtained that the variables of power dominance in the household were related to the decision-making of the IVA TEST examination (p = 0.042). Socioeconomic variables consisting of education and income have no relationship with the decision-making to perform the IVA TEST examination. In contrast, knowledge relates to the decision-making to perform the IVA TEST examination (p=0.026). The patriarchal cultural variable of access to resources has no relationship with the decision-making to conduct the IVA TEST examination. In contrast, access to health facilities relates to the decision to run the IVA TEST examination (p=0.048).